The NW extension of the Nahavand Fault along the Main Recent Fault, west Iran - Reza Alipoor; Ehsan Aghayani (PLoS ONE, 2025)
The MRF (Main Recent Fault) is an active fault zone in the western Iranian Plateau. The Nahavand Fault, an active 80-km segment of the MRF, lies between the Sahneh Fault to the northwest and the Qaleh-Hatam and Dorud faults to the southeast. The aim of this study is to examine the northwestern extension of the Nahavand Fault beneath Quaternary alluvial deposits. For this purpose, detailed field studies were conducted on a trench excavated perpendicular to the fault’s strike to determine the fault plane’s mechanism and characteristics. Additionally, data from the interpretation of two geoelectrical profiles were used to locate the surface trace of the fault beneath the alluvial deposits. The results indicate that, at the southeastern termination of the Nahavand Fault, the transpression stress regime has been overprinted by a transtensional regime. At its northwestern termination, the Nahavand Fault connects with the Sahneh Fault via a fault-bend pattern. The characteristics of the Nahavand Fault beneath the alluvial deposits of the Nahavand plain are N70°W/75°NE, with a rake of 15°. The Nahavand Fault extends northwestward with an updated length of approximately 80 km.